The effectiveness of vocational rehabilitation on work participation: a propensity score matched analysis using nationwide register data - Leinonen, Taina; Viikari-Juntura, Eira; Husgafvel-Pursiainen, Kirsti; Juvonen-Posti, Pirjo; Laaksonen, Mikko; Solovieva, Svetlana (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVE ': 'Research on the effectiveness of vocational rehabilitation has focused on small and selected groups, lacked proper controls, or not captured dynamic changes in work participation. Using rich nationwide data on vocational rehabilitees and matched controls, long-term changes in work participation before and after vocational rehabilitation were examined to assess its effectiveness. ' ' METHODS ': 'Representative Finnish register data were used to examine 3199 recently employed individuals aged 30–55 years with histories of musculoskeletal- and mental-related work disability starting vocational rehabilitation in 2008–2010 (intervention group), and 3199 propensity score matched non-rehabilitees (control group). Sociodemographic and work-related factors and detailed 3-year work disability and other labor market history were used for matching. Generalized estimation equations were used to examine differences in the proportion of time spent at work between periods before and after rehabilitation among the intervention and control group and the difference in these differences (DID). ' ' RESULTS ': 'Vocational rehabilitation resulted in gains in work participation, the total 1-, 2-, and 3-year DID being 11.8 [95% confidence interval (CI) 10.0–13.7], 8.9 (95% CI 7.6–10.2), and 7.2 (95% CI 6.1–8.3) percentage points, respectively. Contrary to this overall pattern, larger DID was observed over the long term for those whose rehabilitation lasted >10 months. The DID was lowest among women with musculoskeletal diseases. ' ' CONCLUSIONS ': 'Vocational rehabilitation after musculoskeletal- or mental-related work disability showed modest effectiveness on work participation. To promote sustained work participation after shorter rehabilitation (likely comprising workplace interventions) and faster work resumption after longer rehabilitation (likely comprising training), enhanced and complementary interventions should be considered.
Keywords: employment; Finland; labor market status; matched analysis; mental disorder; musculoskeletal disease; occupational rehabilitation; propensity score; quasi-experimental study; register data; rehabilitation; return to work; vocational rehabilitation; work disability; work participation